1999
DOI: 10.1116/1.581989
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional CT images of two-frequency capacitively coupled plasma

Abstract: Two-dimensional images of two-frequency capacitively coupled plasma (2f-CCP) in Ar and Ar/CF4(5%) in an axisymmetric parallel plate reactor are investigated by using 2D-t optical emission spectroscopy. Spatially averaged electron density is obtained by microwave interferometry. Results are presented in the form of 2D profiles of the net excitation rate of Ar(3p5)(εex=14.5 eV) and Ar+(4p4D7/2)(εex=35.0 eV) used as a probe. Large area uniformity of plasma production driven at very high frequency (VHF) (100 MHz) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 28 publications
2
62
0
Order By: Relevance
“…In our series of experiments, 7,8,19 we found that the radial profile of ⌳ j (z,r) is considerably affected by the field distribution close to the edge of the powered electrode, i.e., the arrangement of the cylindrical metal electrode, outer insulator and the surrounding metal shield grounded to the earth, in a low-pressure and in a low-density RIE. The simple geometry of the reactor used in the modeling is different, in detail, in the radial frame with the experimental RIE, in order to save computing time.…”
Section: B Modeling Validitymentioning
confidence: 98%
“…In our series of experiments, 7,8,19 we found that the radial profile of ⌳ j (z,r) is considerably affected by the field distribution close to the edge of the powered electrode, i.e., the arrangement of the cylindrical metal electrode, outer insulator and the surrounding metal shield grounded to the earth, in a low-pressure and in a low-density RIE. The simple geometry of the reactor used in the modeling is different, in detail, in the radial frame with the experimental RIE, in order to save computing time.…”
Section: B Modeling Validitymentioning
confidence: 98%
“…In material processing, plasma sheath width and sheath potential are crucial for anisotropic ion motion and etch rate [1]- [12]. In order for better control of the sheath parameters and ion energy distribution (IED), a new generation of capacitively coupled plasma driven by multi-frequency RF source has become a subject of much scientific interests [2]- [5]. Goto et.…”
Section: Introductionmentioning
confidence: 99%
“…The plasma sources developed so far for production of large-area plasmas include capacitively-coupled plasmas (CCP) [1][2][3][4], inductivelycoupled plasmas (ICP) [1,[5][6][7][8][9] and surface wave plasmas (SWP) [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%